Collaboration in a Virtual Reality Serious Escape Room in the Metaverse Improves Academic Performance and Learners’ Experiences - Antonia-Maria Pazakou; Stylianos Mystakidis; Ioannis Kazanidis (Future Internet)
The evolving potential of virtual reality and the Metaverse to create immersive, engaging learning experiences and of digital escape room games to provide opportunities for active, autonomous, personalised learning has brought both to the forefront for educators seeking to transform traditional educational settings. This study investigated the impact of collaboration within a virtual reality serious escape room game in the Metaverse that was designed for English as a Foreign Language (EFL) learners to explore how this approach influences their academic performance and overall learning experience. A comparative research approach was adopted using twenty (n = 20) adult learners divided into two equal-sized groups; the experimental group completed the virtual reality escape room in pairs, while the control group completed it individually. Mixed methods were employed, utilising a pre- and post-test to measure academic performance, as well as a questionnaire and two focus groups to evaluate participants’ learning experiences. Results indicated a trend of learners working collaboratively showing better learning outcomes and experience, offering valuable insights regarding the integration of serious Metaverse games in language-focused educational contexts.